Dielectric properties of PLZT-x/65/35 (2 ≤ x ≤ 13) under mechanical stress, electric field and temperature loading - Pytel, K.; Suchanicz, J.; Livinsh, M.; Sternberg, A. (Condensed Matter Physics, 2013)
We investigated the effect of uniaxial pressure (0÷1000 bars) applied parallely to the ac electric field on dielectric properties of PLZT-x/65/35 (2≤x≤13) ceramics. There was revealed a significant effect of the external stress on these properties. The application of uniaxial pressure leads to the change of the peak intensity of the electric permittivity (ϵ), of the frequency dispersion as well as of the dielectric hysteresis. The peak intensity ϵ becomes diffused/sharpened and shifts to a higher/lower temperatures with increasing the pressure. It was concluded that the application of uniaxial pressure induces similar effects as increasing the Ti ion concentration in PZT system. We interpreted our results based on the domain switching processes under the action of combined electromechanical loading. Ми дослiдили вплив одновiсного тиску (0÷1000 bars), прикладеного паралельно до змiнного електричного поля, на властивостi керамiки PLZT-x/65/35 (2≤x≤13). Виявлено значний вплив зовнiшнього напруження на цi властивостi. Прикладання одновiсного тиску веде до змiни пiку iнтенсивностi електричної проникностi ("), частотної дисперсiї i дiелектричного гiстерезису. Пiк iнтенсивностi " стає розмитий/загострений i зсувається до вищих/нижчих температур з ростом тиску. Робиться висновок, що прикладання одновiсного тиску iндукує подiбнi ефекти як пiдвищення концентрацiї iонiв Ti в системi PZT. Ми iнтерпретуємо нашi результати на основi процесiв перемикання доменiв пiд дiєю комбiнованого електромеханiчного навантаження.